1990
DOI: 10.1007/bf00145815
|View full text |Cite
|
Sign up to set email alerts
|

Convergent strabismus fixus in high myopic patients

Abstract: Patients with high myopia may develop a myopathy which frequently results in a sort of convergent strabismus fixus. Echographic and CT scan findings give evidence that a myopathic paralysis of the lateral rectus is supported by a slow pressure on this muscle squeezed between the lateral orbital wall and the enlarged eyeball.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 4 publications
(7 reference statements)
1
24
0
4
Order By: Relevance
“…BagIn our clinical practice, we were often in doubt about our results. Because in myopic patients some muscles such olini et al [7] suggested that pressure of the large globe on the lateral rectus muscle resulted in paralysis of the as the lateral rectus can be reduced in size, in accordance with different authors' results, pathologic values can be muscle with esotropia in 6 patients. They proposed that in addition to the paralysis of the lateral rectus muscle, considered normal by mistake.…”
Section: Introductionsupporting
confidence: 65%
“…BagIn our clinical practice, we were often in doubt about our results. Because in myopic patients some muscles such olini et al [7] suggested that pressure of the large globe on the lateral rectus muscle resulted in paralysis of the as the lateral rectus can be reduced in size, in accordance with different authors' results, pathologic values can be muscle with esotropia in 6 patients. They proposed that in addition to the paralysis of the lateral rectus muscle, considered normal by mistake.…”
Section: Introductionsupporting
confidence: 65%
“…They range from an inflammatory disease, which causes an atrophy of the lateral recti muscles, to a mechancal lesion of these muscles due to a contact of the enlarged and deformed eyeball with the orbital wall. [6][7][8][9][10][11][12] Currently, the most accepted theory, first proposed by Krzizok,13 suggests that a progressive prolapse of the posterior portion of the eyeball to the superotemporal quadrant of the orbit, outside of the tissues with support function (pulley) and the muscular cone, occurs in patients with high myopia. The prolapsed portion of the bulb causes a nasal displacement of lateral rectus (LR) muscle toward the bottom and superior rectus (SR) muscle nasally.…”
Section: Introductionmentioning
confidence: 99%
“…Bagolini et al (12) , estudando 6 pacientes com "síndrome da esotropia miópica adquirida progressiva", notaram que todos os olhos tinham comprimeto axial aumentado e alta miopia. Os pacientes foram submetidos a TC e ecografia, através do que mediram os espaços entre a parede orbitária lateral e o bulbo.…”
Section: Comentáriosunclassified
“…Estudos histológicos do reto lateral de pacientes esotró-picos míopes revelaram, através de microscopia eletrônica, presença de fibrose e aumento do tecido conectivo intersticial, com espessamento da membrana basal do endotélio capilar (7,(12)(13) . A redução da função muscular, associada à miopia progressiva, demonstrada nesses trabalhos, sugere a hipótese de tratar-se de paresia miogênica.…”
Section: Comentáriosunclassified